Significant life experience, psychological well-being, and resilience in high performance students from high vulnerability contexts. A comparative study - Morales, Mario (2017)
The results are presented of a study comparing high performance High school students with an index of high vulnerability (about 80%) and their normative and non-normative life events, compared with another group of students with poor school performance. The population included 502 students from various schools in the metropolitan area of Chile. The instruments were used: psychological well-being, (BIEP-J), Resilience Scale (SV-RES); and normative and non-normative life events (VVS). Significant differences were found in satisfaction with the school and support application for problem solving; Regarding their psychological well-being differences occurred in the projects and control factors, and the resilience scale in the factors of goals, project, self-efficacy and learning.